HIGHER EDUCATION IN THE EUROPEAN SUSTAINABLE DEVELOPMENT - Іванова, Т. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article deals with the problems of education; particularly higher education; in the context of the European sustainable development; singled out the factors that influence the development of the modern education system and the requirements of modern civilization to the human person